2019
DOI: 10.1371/journal.pone.0222081
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in bovine endometrial epithelial cells after challenge with LPS; specific implications for genes involved in embryo maternal interactions

Abstract: Lipopolysaccharide (LPS) expressed on the surface of Gram-negative bacteria activates pro-inflammatory pathways, dys-regulates the function of endometrial cells and is a key player in the mechanisms involved in endometritis. This study aimed to investigate the effects of LPS on bovine endometrial epithelial cells (bEEC) from whole transcriptome with a special focus on genes involved in embryo-maternal interactions. Following in vitro culture, bEEC from three cows were exposed to 0, 2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 90 publications
1
31
0
Order By: Relevance
“…It was well recognized that a series of genes involved in LPS-induced in ammation [18][19][20]. In this study, the DE mRNAs functional enrichment results showed that these genes were related to some biological processes, including in ammatory response, immune response, cytokine activity, chemokine activity, cytokine-cytokine receptor interaction, TNF signal pathway, NF-κB signal pathway, JAK-STAT signal pathway, NOD-like receptor signal pathway and TLR signal pathway, which were closely associated with LPS-induced in ammation [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…It was well recognized that a series of genes involved in LPS-induced in ammation [18][19][20]. In this study, the DE mRNAs functional enrichment results showed that these genes were related to some biological processes, including in ammatory response, immune response, cytokine activity, chemokine activity, cytokine-cytokine receptor interaction, TNF signal pathway, NF-κB signal pathway, JAK-STAT signal pathway, NOD-like receptor signal pathway and TLR signal pathway, which were closely associated with LPS-induced in ammation [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…We chose P6 stromal cells. Previous study using P5 bovine endometrial epithelial cells to investigate effects of LPS on whole transcriptome with a special focus on genes involved in embryo-maternal interactions [23]. And transcriptome profiling analysis of on P6 bovine vaginal epithelial cell response to an isolated lactobacillus strain [24].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have been performed on RNA-seq analysis of effects of LPS on whole transcriptome of bovine endometrial epithelial cells with focus on genes involved in embryo-maternal interactions. They identified 2,035 and 2,073 DEGs in control cells and cells treated with LPS [23]. However, comprehensive transcriptomic analysis of response of bovine endometrial stromal cells to LPS by RNA-seq remains to be elucidated.…”
mentioning
confidence: 99%
“…Transcriptome analyses of pretransfer embryos and the endometrium identified several genes with potential indicator to pregnancy success in cattle (Salilew-Wondim et al 2010). Another study reported over expression of several immune-related genes including cytokines in the bovine endometrium as a result of lipopolysaccharide (LPS) treatment (Guo et al 2019). Brooks et al (2016) evaluated gene expression profiles of the endometrium during early pregnancy in sheep.…”
Section: Introductionmentioning
confidence: 99%